Disrupted Resting-State Default Mode Network in Betel Quid-Dependent Individuals - Zhu, Xueling; Zhu, Qiuling; Jiang, Canhua; Shen, Huaizhen; Wang, Furong; Liao, Weihua; Yuan, Fulai (Frontiers in Psychology, 2017)
Recent studies have shown that substance dependence (addiction) is accompanied with altered activity patterns of the default mode network (DMN). However, the neural correlates of the resting-state DMN and betel quid dependence (BQD)-related physiopathological characteristics still remain unclear. Resting-state functional magnetic resonance imaging images were obtained from 26 BQD individuals and 28 matched healthy control subjects. Group independent component analysis was performed to analyze the resting state images into spatially independent components. Gray matter volume was examined as covariate with voxel-based morphometry to rule out its effect on the functional results. The severity of BQD was assessed by the BQD scale. We observed decreased functional connectivity in anterior part of the DMN including ventral medial prefrontal cortex (VMPFC), orbital MPFC (OMPFC)/ anterior cingulate cortex (ACC). Furthermore, the functional connectivity within the OMPFC/ACC in BQD individuals was negatively correlated with BQD scores ( p = 0.01, r = -0.49). We reported decreased functional connectivity within anterior part of the DMN in BQD individuals, which provides new evidence for the role of the DMN in the pathophysiology of BQD.